Gross Anatomy: Are Anatomical Models Worth the Investment? - Harmon, Geoffrey James Corey; Roby, Mary (My University, 2019)
Our library began its anatomical model collection in the late 1980s with one model of the fetus. In intervening years, the collection has grown to 236 models ranging from single organs to entire bodies. As of July 1, 2019, the circulation count for the models was 17,944. During the 2018-2019 academic year, we observed that several of the models had become too damaged to continue circulating and we evaluated whether to replace them or slowly discontinue the service. Based on circulation numbers, as well as anecdotal evidence such as the results of an informal survey of model requests from students, we chose to replace the damaged models and expand the collection further. Methods: We will supplement our previously collected data with empirical methods to provide additional evidence to inform future decisions about continued investments in the anatomical model lending program. We will examine the types of patrons using the models, each model’s usage statistics, and their cost per use. As a comparison, we will look at the statistics for our virtual anatomy subscriptions. We will list the academic programs that have most frequently used the models, survey the faculty who teach relevant classes in those programs about their perception of value added for their students, and survey the students who check out the physical models regarding their assessment of this program’s value to them. Finally, we will survey the other academic health science libraries in the MAC region about their physical model collection and its usage, and search the literature to find other evidence of the value that models provide in health sciences education.
Keywords: Libraries; Anatomical Models